1985
DOI: 10.1080/0267257x.1985.9963976
|View full text |Cite
|
Sign up to set email alerts
|

The Methuselah market

Abstract: In this paper the authors focus on the Methuselah Market, defined as those people within five years of retirement age. Demographic change over the last 100 years has led to a substantial increase in the proportion of the population in the older, near retirement age group. Yet as consumers the needs of this sector of the population have been neglected by marketers. The size, characteristics and potential of the Methuselah Market are discussed, and specific product areas of particular interest to this market are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…In terms of UK older consumers, only one study (Tynan and Drayton, 1985a, b) identified a potentially important segment for a variety of products and services, known as “Methuselahs”, which although it had some similarities to Schiffman and Sherman's (1991) American “new age elderly”, it also exhibited significant differences. Other than Tynan and Drayton's work, there is only one known piece of commercial research to have identified segments of older UK consumers (Silman and Poustie, 1994), which used the target group index to identify five segments which differ solely on the basis of attitudes toward money, travel, and media.…”
Section: Segmentation Of Older Consumersmentioning
confidence: 99%
“…In terms of UK older consumers, only one study (Tynan and Drayton, 1985a, b) identified a potentially important segment for a variety of products and services, known as “Methuselahs”, which although it had some similarities to Schiffman and Sherman's (1991) American “new age elderly”, it also exhibited significant differences. Other than Tynan and Drayton's work, there is only one known piece of commercial research to have identified segments of older UK consumers (Silman and Poustie, 1994), which used the target group index to identify five segments which differ solely on the basis of attitudes toward money, travel, and media.…”
Section: Segmentation Of Older Consumersmentioning
confidence: 99%
“…The traditional approaches to segmenting older consumers involve the use of demographic, socio-economic and psychographic variables such as: age bands (Treguer, 2002), lifestyle segmentation variables (Hesse, 1991), gerontographics (Moschis, 1993(Moschis, , 1996, level of professional and social activity (Weijters and Geuens, 2003), benefit segmentation (Haley, 1984;Tynan and Drayton, 1985;Loker and Perdue, 1992), discretionary income, discretionary time, response to others, and state of health (Bone, 1991).…”
Section: Segmenting the Grey Marketmentioning
confidence: 99%
“…Traditionally the 'older consumer' has been described as neglected, rarely being offered products or services specifically developed or marketed towards their needs (Phillips & Sternthal, 1977). This is despite being healthy, active consumers and providing many opportunities for marketers and the economy (Tynan & Drayton, 1985). Recent debates have acknowledged the importance of further understanding the lived experiences of ageing consumers, with a view to capturing product use in relation to well-being (Ford et al, 2016;Stone & Gould, 2016).…”
Section: Introductionmentioning
confidence: 99%